Partnerstwo lokalne/regionalne jako forma praktycznej realizacji koncepcji governance w zarządzaniu jednostką terytorialną - Rudolf, Wawrzyniec (Local/Regional Partnership as a Form of the Implementation of Governance in Territorial Management, 2008)
The article concerns the public governance, which is the fashionable, in the Western countries, but not yet popular in Poland concept applied to public administration. The literature analysis resulted in the conclusion that the term is differently understood by different authors and it is very capacious. The author proposes the new Polish translation of governance "współrządzenie", which has wider meaning than the previously used term „rządzenie". It is the European Union which tries to use the potential of governance in its multilevel policy. The Union also actively promotes this concept among Member States and territorial self-governments. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 440-448